Masson pine pollen aqueous extract ameliorates cadmium-induced kidney damage in rats - Hu, Zhiyong; Chen, Sixin; Shi, Tala; Dong, Zhaoju; Cheng, Mei; Li, Ning; Zhao, Huijuan; Zhu, Haibo; Han, Chunlei; Xu, Lanlan (Frontiers in Molecular Biosciences, 2023)
Introduction: Cadmium (Cd) is a hazardous environmental pollutant present in soil, water and food. Accumulation of Cd in organisms can cause systematic injury and damage to kidney. Masson pine pollen aqueous extract (MPPAE) has attracted increasing attention due to its antioxidant activity and ability to enhance immunity.In this study, we investigated the potential of MPPAE to protect against Cd-induced kidney damage in rats and the underlying mechanism. The transcriptome and metabolome of rats with Cd-induced kidney damage following treatment with MPPAE were explored.The concentrations of superoxide dismutase (SOD) and malonaldehyde (MDA), were both significantly altered after treatment with MPPAE. Furthermore, sequencing and analysis of the transcriptome and metabolome of rats with Cd-induced kidney damage following treatment with MPPAE revealed differential expression of numerous genes and metabolites compared with the untreated control rats. These differentially expressed genes included detoxification-related genes such as cytochrome P450 and transporter. The differentially expressed metabolites included 4-hydroxybenzoic acid, L-ascorbate and ciliatine. Conjoint transcriptome and metabolome analysis showed that several differentially expressed genes were correlated with differentially expressed metabolites.These preliminary findings indicate the potential of MPPAE for the treatment of toxic metal poisoning.